Work engagement: the role of emotional intelligence to employee: Work engagement: peran kecerdasan emosi pada karyawan - Febrina, Shinta Febrina; Unandari; Hartika, Dina (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
This study aims to determine the contribution of emotional intelligence to work engagement. The subjects in this study were 52 employees who worked in clothing stores and filled out the emotional intelligence scale and Utrecht-work engagement scale. The data analysis method used a simple linear regression technique. Based on data analysis, in testing the hypothesis contribution of emotional intelligence to work engagement, the analysis revealed a significant contribution of emotional intelligence to work engagement in 59.9%, and the remaining 40.1% were other factors beyond the study. The lower the emotional intelligence is, the lower the work engagement. We suggested that the next researcher study emotional intelligence and work engagement in another field of work or another type of industry. The implication of this research is for the company to develop emotional intelligence first to increase work engagement.